Out of my heart - Draper, Sharon M. (Sharon Mills) (2021)
Because she loves horses but is scared of them, Melody wants to conquer her fears, so she hopes a summer camp will be the place to welcome someone with cerebral palsy who wants to learn to ride
"A Caitlyn Dlouhy Book."
a
Keywords: People with disabilities -- Juvenile fiction; Cerebral palsy -- Juvenile fiction; Self-confidence -- Juvenile fiction; Horsemanship -- Juvenile fiction; Camps -- Juvenile fiction; Bildungsromans; Realistic fiction